Analisis Sektor Basis dalam Hubungannya dengan Penyerapan Tenaga Kerja di Kabupaten Batang Hari - Syaiful Syaiful; Syaparuddin Syaparuddin; Dearmi Artis (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
The purpose of the study is to (1) analyze the economy sector which become basis sector with its development rates in Batang Hari Regency, (2) the correlation between the developments of basis sector with employment and to (3) analyze the policy of local government on developing that basis sector through bibliography methods on secondary PDRB data according to constant price 2000 of Batang Hari Regency and Jambi Province from 2003 to 2012 and also employment data in the same periods and regency.  This analysis uses Location Quotient (LQ) model and Dynamic Location Quotient (DLQ) model.  Whereas the correlation between the developments of basis sector with employment uses Pearson’s Coefficient Of Correlation. The output of LQ analysis shows that there are four economy sectors as basis sector (LQ >1) in Batang Hari, which are agricultures, industry and manufactures, trades, hotels, restaurants, and another distinction service. While from the DLQ analysis, there are four sectors identified can be a basis sector in the future (DLQ >1), which are mining and excavation, electricity, gases and fresh water, transportation and communications, and distinction sectors.  Only distinction sector which is identified as basis sector nowadays as well as in the future.  From the study of the PDRB rate in Batang Hari from 2003 to 2013 shows that average growth rate of agriculture, industry and manufactures, trades, hotels and restaurants are relatively smaller than other sectors in Batang Hari, excluding distinction sectors which are higher. Pearson’s Coefficient Of Correlation analysis evinces there only two basis sectors which its growth has a strong and positive correlation with employment in Batang Hari, which are distinction and trades with hotels and restaurants. The PDRB growth of these sectors moving in the direction of the employment rates.  In the agriculture and manufacture industry sectors, the correlation with employment is low and very weak. Keywords: competitive, basis sector, agriculture, manufacture